RAPD analysis in the Neotropical fish Brycon lundii: Genetic diversity and its implications for the conservation of the species - Pinto Wasko, Adriane [UNESP]; Galetti Jr., Pedro Manoel (My University, 2002)
Random amplified polymorphic DNA (RAPD) technique was used to examine the genetic variability on an endangered Neotropical fish species, Brycon lundii, collected on two regions with distinct environmental conditions in the São Francisco River (Brazil), downstream from a hydroelectric station. Using decamer oligonucleotides as single primers in Polymerase Chain Reaction (PCR), genetic similarity index, mean allele frequency and mean heterozigosity were estimated, revealing variations between samples from the two regions. Moreover, a fragment of about 1200 base pairs was found in 100% of the examined animals collected at the region closer to the hydroelectric dam, while its frequency was much lower (27.3%) within the sample from the second collecting site, 30 km downstream from the dam, indicating a possible correlation between genetic variation and geographical area. A dendogram representing the relationships among genotypes was obtained, demonstrating at least two major clusters of animals. Based on the data, a model of population structuring in Brycon lundii is suggested. The described approach holds great promise for further analyses and gives support to biodiversity maintenance and recovery efforts of B. lundii.
Keywords: Brycon lundii; Conservation genetics; Genetic variability; Random amplified polymorphic DNA (RAPD); DNA; Hydroelectric power; Mean allele frequency; Biodiversity; conservation genetics; endangered species; fish; genetic variation; Brazil; Animalia; Brycon